2020
DOI: 10.1042/bst20200224
|View full text |Cite
|
Sign up to set email alerts
|

Driving antimalarial design through understanding of target mechanism

Abstract: Malaria continues to be a global health threat, affecting approximately 219 million people in 2018 alone. The recurrent development of resistance to existing antimalarials means that the design of new drug candidates must be carefully considered. Understanding of drug target mechanism can dramatically accelerate early-stage target-based development of novel antimalarials and allows for structural modifications even during late-stage preclinical development. Here, we have provided an overview of three promising… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 99 publications
(167 reference statements)
0
4
0
Order By: Relevance
“…π–π interactions are observed between the naphthyl portion and residues Phe227 and Phe188. These interactions are made possible because the naphthyl binding site allows the approximation of a pocket that arises from a considerable rotation of Phe188, denoting an interpretation that the Pf DHODH enzyme is capable of binding to several chemical classes with high affinity. , Mutations F188L and F188I show high-level resistance to Pf DHODH inhibitors, suggesting that the aromatic ring of phenylalanine forms more conducive interactions with inhibitors. In addition, Phe188 acts as a gate for docking in the pocket of the inhibitor binding site …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…π–π interactions are observed between the naphthyl portion and residues Phe227 and Phe188. These interactions are made possible because the naphthyl binding site allows the approximation of a pocket that arises from a considerable rotation of Phe188, denoting an interpretation that the Pf DHODH enzyme is capable of binding to several chemical classes with high affinity. , Mutations F188L and F188I show high-level resistance to Pf DHODH inhibitors, suggesting that the aromatic ring of phenylalanine forms more conducive interactions with inhibitors. In addition, Phe188 acts as a gate for docking in the pocket of the inhibitor binding site …”
Section: Resultsmentioning
confidence: 99%
“…Unconventional hydrogen interactions were observed with the three ligands DSM483 [iii­(C16)­O], DSM1- Pf DHODH [ii­(N5)­C], and DSM1- Pf DHODH­(C276F) [i­(C14)­H], in addition to more alkyl interactions, alkyl with DSM483 [iii­(C17)­H] were analyzed. Val532 is part of a small hydrophobic channel also formed by Ile272 and Ile263. , The analysis of interactions between Pf DHODH and ligands showed that Val532 forms an important H binding with inhibitors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmodium falciparum dihydrofolate reductase-thymidylate synthase (pfDHFR-TS) is a well-known homodimeric enzyme with DHFR and thymidylate synthase (TS) domain residues. pfDHFR-TS produces folates and thymidylate (dTMP), both of which are required for DNA synthesis, and has been studied extensively in order to develop effective antimalarial drugs [ 57 ].…”
Section: Methodsmentioning
confidence: 99%